FACTOR INFLUENCE THE UNIVERSITY STUDENTS' INTEREST USING E-WALLET AS A THE PAYMENT METHOD - Dwi Puspita; Almasdi Syahza; Brilliant Asmit (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The emergence of technology has led to a shift from traditional cash payment methods to non-cash payments. With this in mind, a study has been conducted to investigate the growing interest of university students in using e-wallets for payments. The study aims to determine the factors influencing students’ interest in using e-wallets. The literature review narrowed the investigation to two factors, usefulness and security. The population for this study is university students who use e-wallets. Data collection was carried out through a survey by distributing questionnaires to respondents. For data analysis methods using descriptive analysis and multiple linear regression analysis. The study results indicate that usefulness is the most dominant factor influencing student interest in using e-wallets. This research is expected to provide benefits as new knowledge about e-wallets and the basis for further researchers to deepen the scope of understanding adopting e-wallets, besides that it is also expected to be used by interested parties to improve the e-wallet system based on the results of emprise research.